Tenggang waktu Pengajuan Permohonan Fiktif Positif berdasarkan UU NO 8 Tahun 2017 - Mu'ala, Abdulloh Afifil; Rochman, Muhammad Habibur (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
Abstract Positive fiction is the silent attitude of the State Administrative Body or Official (TUN) towards State Administrative Decision that are intangible and considered as granting the submitted request. Provisions regarding Positive Fictional Decisions are stipulated in Article 53 of the Administrative Court Law (UUAP) and Supreme Court Regulation No. 8 of 2017. In Positive Fictional Decisions, there is a time limit of 10 (ten) working days after the request is received. This study examines the mechanism of the time limit for Positive Fictional Requests based on the Law on Government Administration Number 30 of 2014 concerning Government Administration, and the time limit process in one example of a positive fictional request case against Decision Number: 17/P/FP/2019/PTUN.SBY at the State Administrative Court in Surabaya based on Law Number 8 of 2017 concerning Procedural Guidelines for Obtaining Decisions on the Acceptance of Requests to Obtain Decisions on the Actions of Government Bodies or Officials. In addressing this issue, the author uses a normative juridical approach. The method involves analyzing legal concepts, legislation, and case studies related to the decision. In collecting data, the author uses the method of collecting data through document/library research. The results of this study emphasize the need to provide awareness to Government Officials about the importance of responding to requests within a period of 10 (ten) working days. There is also a necessity to establish implementing regulations for the Law on Government Administration, which detail, explain, and emphasize the norms in each provision, particularly those related to expansions found in Law Number 8 of 2017 concerning Procedural Guidelines for Obtaining Decisions on the Acceptance of Requests to Obtain Decisions on the Actions of Government Bodies or Officials. Abstrak Fiktif Positif merupakan sikap diam Badan atau Pejabat TUN pada Keputusan TUN yang tidak berwujud dan dianggap mengabulkan permohonan yang telah diajukan. Ketentuan mengenai Keputusan Fiktif Positif terdapat dalam Pasal 53 UUAP dan Perma No. 8 Tahun 2017. Dalam keputusan Fiktif Positif terdapat tenggang waktu 10 (sepuluh) hari kerja setelah permohonan diterima. Dalam penelitian ini mengkaji tentang mekanisme tenggang waktu Permohonan fiktif positif berdasarkan Undang-Undang Administrasi Pemerintahan Nomor 30 Tahun 2014 tentang Administrasi Pemerintahan, dan proses tenggang waktu pada salah satu contoh perkara permohonan fiktif positif terhadap Putusan Nomor : 17/P/FP/2019/PTUN.SBY di Pengadilan Tata Usaha Negara Surabaya Berdasarkan Undang – Undang Nomor 8 Tahun 2017 Tentang Pedoman Beracara Untuk Memperoleh Putusan Atas Penerimaan Permohonan Guna Mendapatkan Keputusan Atas Tindakan Badan Atau Pejabat Pemerintahan. Dalam persoalan tersebut, penulis menggunakan pendekatan yuridis normatif. Menggunakan metode pendekatan analisis konsep hukum, analisis perundang-undangan, dan pendekatan kasus yang berkaitan dengan Putusan Dalam pengumpulan data, mempergunakan metode pengumpulan data melalui studi dokumen/ kepustakaan (library research). Hasil penelitian ini adalah memberikan sosialisasi kepada Penjabat Pemerintahan tentang pentingnya menanggapi Permohonan dalam kurung waktu 10 (sepuluh) hari kerja. Perlunya dibuat peraturan pelaksana dari Undang-Undang Administrasi Pemerintahan, yang menguraikan, menjelaskan dan menegaskan mengenai norma-norma dalam setiap ketentuan khususnya terkait dengan perluasan yang terdapat di dalam Undang – Undang Nomor 8 Tahun 2017 Tentang Pedoman Beracara Untuk Memperoleh Putusan Atas Penerimaan Permohonan Guna Mendapatkan Keputusan Atas Tindakan Badan Atau Pejabat Pemerintahan.